2019
DOI: 10.1111/jgs.15966
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Pharmacologic Treatments of Major Depression in Older Adults

Abstract: OBJECTIVES To assess adverse effects of pharmacologic antidepressants for treatment of major depressive disorder (MDD) in adults 65 years of age or older. DESIGN Systematic review and meta‐analysis. SETTING Specialist or generalist outpatient setting, rehabilitation facility, and nursing facilities. PARTICIPANTS Persons 65 years and older with MDD. INTERVENTION Selective serotonin reuptake inhibitors (SSRIs), serotonin norepinephrine reuptake inhibitors (SNRIs), bupropion, mirtazapine, trazodone, vilazodone, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 54 publications
1
71
0
3
Order By: Relevance
“…33 On the other hand, depression is amenable to medication therapy, yet fewer than 30% of patients in this study received antidepressants at EOL-1, which is low relative to symptom prevalence in this population. Clinicians may be reluctant to prescribe antidepressants to older adults because of risk of major adverse events such as falls or fractures, 34 intolerable side effects such as nausea and dizziness, or lack of time to receive benefit if prognosis is poor. 35 When we combine antidepressants and anxiolytics, we find that almost half of our study patients received medications for emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…33 On the other hand, depression is amenable to medication therapy, yet fewer than 30% of patients in this study received antidepressants at EOL-1, which is low relative to symptom prevalence in this population. Clinicians may be reluctant to prescribe antidepressants to older adults because of risk of major adverse events such as falls or fractures, 34 intolerable side effects such as nausea and dizziness, or lack of time to receive benefit if prognosis is poor. 35 When we combine antidepressants and anxiolytics, we find that almost half of our study patients received medications for emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these medications are indicated as first-line therapy for the treatment of depression. A few studies suggested that SSRIs are prescribed more often as the first medication used to treat depression [11,15]. It was not expected that there would be a significant difference in patient experience, and, thus, no difference in ratings was expected.…”
Section: Discussionmentioning
confidence: 99%
“…MDD can develop at any age, and is considered the leading cause of disability in the US for individuals between the ages of 15 and 44. [2][3][4] The two most commonly used treatments for MDD are antidepressants (87.0%) and psychotherapy (23.2%). 5 Several known challenges have been faced by these treatment approaches: 1) frequent relapses of the cognitive therapy 6 and 2) burdensome side-effects of antidepressant medication.…”
Section: Introductionmentioning
confidence: 99%
“…15 A wide range of studies, in both animal models and humans, have shown that PBM causes minimal or no adverse effects while producing therapeutic effects. 10,16,17 Although MDD has a broad age of onset, 2,4 most previously published studies have focused on t-PBM treatments in only middle-aged adult brain models. 18 However, personalization of treatments is key to increasing success rate and tolerability; therefore our interest is in developing precise PBM treatment strategies adapted for individual patients.…”
Section: Introductionmentioning
confidence: 99%